2(x-3)+4(x+5)=6x

Simple and best practice solution for 2(x-3)+4(x+5)=6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-3)+4(x+5)=6x equation:



2(x-3)+4(x+5)=6x
We move all terms to the left:
2(x-3)+4(x+5)-(6x)=0
We add all the numbers together, and all the variables
-6x+2(x-3)+4(x+5)=0
We multiply parentheses
-6x+2x+4x-6+20=0
We add all the numbers together, and all the variables
14!=0
There is no solution for this equation

See similar equations:

| -11+5=3y | | 7(g+6)=56 | | n-3=12÷3 | | 9(d+6)=72 | | -6+-3a=0 | | 8(m-3)=-24+8m | | 1/2b+15=45 | | 19p−18p=6 | | -7(1-4m=13(2m-3 | | -3/4=5/6x+4 | | -6(4-9)=x | | 4x+2=1x-5 | | -2y-6=9y+16 | | 8+x/(-4)=5 | | 8+x÷(-4)=5 | | 9=0.3x | | -2(8+5n)-8n=-106 | | -7(6-3x)=-294 | | 5x-12+5x-12+3x-4=180 | | 3m-1=-19+19m-14m | | 8v-7=13 | | -7(7x+1)=-7 | | 5/6x+4=-3/4 | | 3x-12+5x-12+3x-4=180 | | 5(1-2y)+3y=-23 | | 53=-7s-s+5 | | 5(x+6)=180 | | -108=-3(8x-4) | | 8+3i+5i=16 | | 0.25/n=12 | | 25=2h-5h-2 | | 21+6v=7(-6v+3) |

Equations solver categories